High Efficacy on the Death of Breast Cancer Cells Using SPMHT with Magnetite Cyclodextrins Nanobioconjugates - Costica Caizer; Isabela Simona Caizer-Gaitan; Claudia Geanina Watz; Cristina Adriana Dehelean; Tiberiu Bratu; Codruța Soica (MDPI AG, 2023)
In this study, we present the experimental results obtained in vitro on the human breast adenocarcinoma cell line (MCF-7) by applying superparamagnetic hyperthermia (SPMHT) using novel Fe3O4-PAA-(HP-γ-CDs) (PAA is polyacrylic acid and HP-γ-CDs is hydroxypropyl gamma-cyclodextrins) nanobioconjugates previously obtained by us. In the in vitro SPMHT experiments, we used concentrations of 1, 5 and 10 mg/mL of Fe3O4 ferrimagnetic nanoparticles from Fe3O4-PAA-(HP-γ-CDs) nanobioconjugates suspended in culture media containing 1 × 105 MCF-7 human breast adenocarcinoma cells. The harmonic alternating magnetic field used in the in vitro experiments that did not affect cell viability was found to be optimal in the range of 160-378 Gs and at a frequency of 312.2 kHz. The appropriate duration of the therapy was 30 min. After applying SPMHT with these nanobioconjugates under the above conditions, MCF-7 cancer cells died out in a very high percentage, of until 95.11%. Moreover, we studied the field up to which magnetic hyperthermia can be safely applied without cellular toxicity, and found a new upper biological limit H × f ~9.5 × 109 A/m⋅Hz (H is the amplitude and f is the frequency of the alternating magnetic field) to safely apply the magnetic field in vitro in the case of MCF-7 cells; the value was twice as high compared to the currently known value. This is a major advantage for magnetic hyperthermia in vitro and in vivo, because it allows one to achieve a therapy temperature of 43 °C safely in a much shorter time without affecting healthy cells. At the same time, using the new biological limit for a magnetic field, the concentration of magnetic nanoparticles in magnetic hyperthermia can be greatly reduced, obtaining the same hyperthermic effect, while at the same time, reducing cellular toxicity. This new limit of the magnetic field was tested by us in vitro with very good results, without the cell viability decreasing below ~90%.